Explaining Quality Management in the Danish and Swedish Public Health Sectors: Unintended Learning and Deliberate Co-Optation. Issue 12 (14th October 2016) - Örnerheim, Mattias; Triantafillou, Peter
ABSTRACT: This article examines the development of diverse quality systems in the otherwise quite similar Danish and Swedish public health sectors. After decades of numerous piecemeal medical and managerial quality development programs in both countries, a nationwide mandatory accreditation system was introduced in the Danish health services in 2009. Nationwide quality indicator projects are also found in Sweden, but there has been political attempt to introduce a compulsory system. This article seeks to explain this difference. It argues, first, that resistance from the medical professions blocked the introduction of compulsory, nationwide quality systems in both countries for decades. Second, the implementation of the Danish accreditation system was triggered by a combination of unintended policy learning produced by local reforms in two counties and of the Ministry of Health's carefully orchestrated policy process that served to co-opt critical voices in the medical profession.